Titanium Elastic Nailing for Pediatric Tibia Fractures: Do Older, Heavier Kids Do Worse?. Issue 5 (July 2016) - Goodbody, Christine M.; Lee, Rushyuan J.; Flynn, John M.; Sankar, Wudbhav N.
Abstract : Background: Elastic nailing is a common method of fixation for tibial shaft fractures in skeletally immature individuals. Poor outcomes of titanium elastic nails for femoral shaft fractures have been associated with increasing patient age and weight, especially patients weighing >50 kg. Our objective is to determine if there is an upper weight or age limit to the safe and effective use of titanium elastic nails for tibial shaft fractures in the pediatric population. Methods: This is a retrospective cohort study of patients who underwent stabilization of a tibial shaft fracture with titanium elastic nails at a large tertiary-care pediatric trauma center. Data collected included patient demographics, injury characteristics, and radiographic data. Weight groups were stratified as ≥ or <50 kg, and age groups as 14 years or older or less than 14 years old. Malunion was defined as 10 degrees of angulation in either the sagittal or coronal plane. Union was defined as bridging of ≥3 cortices on orthogonal radiographs. A significant difference in time to union was considered to be 3 weeks. Results: Ninety-five patients were included with a mean age of 12.1 years (range, 6 to 16 y) and a mean weight of 50.2 kg (range, 21 to 122 kg). Malunion rate was similar between weight cohorts: 13.3% (6/45) in the ≥50-kg group and 10% (5/50) in the <50-kg group ( P =0.61). Malunion rate was similarly comparable between age groups: 17.6% (6/34) in the 14 years and older group and 8.2% (5/61) in the less than 14-year-old group ( P =0.17). There was no statistically significant difference in time to union between weight or age cohorts. In sum, we did not find a significant difference in the rate of malunion or time to healing between younger and older patients or between lighter and heavier patients. Conclusion: The use of titanium elastic nails for tibial shaft fractures, unlike for other long bone fractures, seems not to be precluded in older and heavier patients. Level of Evidence: Level III.